THE MAIN DRIVERS OF THE MUTUAL INFORMATION EXCHANGE OF ORGANIZATIONS IN THE CONDITIONS OF THE DIGITAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the main mechanisms facilitating mutual information exchange among organizations within the digital economy landscape. It delves into the significance of information exchange in enhancing collaboration and innovation, analyzes existing literature to identify key mechanisms, presents methods employed in facilitating mutual information exchange, and discusses the results and implications of these mechanisms. The article concludes with suggestions for optimizing mutual information exchange in the digital economy for sustainable organizational growth.